2021
DOI: 10.1213/xaa.0000000000001544
|View full text |Cite
|
Sign up to set email alerts
|

Low Prevalence of Designated Lactation Spaces at Hospitals and Ambulatory Surgery Centers in Iowa: An Educational Tool for Graduates’ Job Selection

Abstract: Many anesthesiologists and nurse anesthetists want to continue breastfeeding their babies when returning to work from maternity leave. The cornerstone of breast milk supply maintenance is breast milk pumping sessions at regular intervals. These breast milk pumping sessions require time and private space for lactation. We surveyed Iowa hospitals and ambulatory surgery centers and created an educational spreadsheet to guide inquiry and postgraduate job selection of our anesthesiology residents and nurse anesthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…While motivated anesthesia departments can fix the lack of convenient lactation space, 1,3 there are fundamental attributes of surgery and anesthesia that functionally impair time for breast milk pumping. 4,5,9 Specifically, patients under anesthesia have continuous care (eg, not like having a patient wait briefly in an examination room, surgery is not interrupted for provider convenience, and there is substantial variability in the duration of surgeries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While motivated anesthesia departments can fix the lack of convenient lactation space, 1,3 there are fundamental attributes of surgery and anesthesia that functionally impair time for breast milk pumping. 4,5,9 Specifically, patients under anesthesia have continuous care (eg, not like having a patient wait briefly in an examination room, surgery is not interrupted for provider convenience, and there is substantial variability in the duration of surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…Those questions (ie, those related to wearable pumps) were not visible until respondents had completed preceding items (Table and Supplemental Digital Content, Supplemental Table, http:// links.lww.com/AACR/A527). That preceding information included accessibility to lactation space based on our earlier study 3 and to assess the validity of our findings (Table, footnote c). We did not inquire about policies regarding wearable pumps because Colbenson et al 8 found that >95% of respondents reported either "no policy in place" or "unsure if a policy is in place" "regarding using a wireless, wearable pump in public areas of the workplace.…”
Section: Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…However motivated the person making the daily case assignments may be, there may be few good choices of operating rooms for nurse anesthetists or anesthesiologists returning from maternity leave to receive time for breast milk pumping sessions [ 1 , 2 ]. Especially based on our sensitivity analysis results for staff scheduling, we recommend departments take advantage of the multiple months of pregnancy and maternity leave to revise staff schedules so that lactating women can plan to work at facilities with long-duration cases and close to lactation rooms [ 27 ]. In addition, when staff scheduling is done, there needs to be a consideration for the additional practitioner(s) to give relief for breaks and breast milk pumping sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Women physicians face additional challenges once returning to work, including limited maternity leave, long work hours, lack of lactation facilities, lack of policies/support, limited flexibility in schedules, and increased work-related stressors that may negatively impact milk production [7,[13][14][15][16][17][18]. Unfortunately, women physicians also experience stigma and discrimination when breastfeeding/pumping [15,16,19,20].…”
Section: Introductionmentioning
confidence: 99%